2012
DOI: 10.3791/3750
|View full text |Cite
|
Sign up to set email alerts
|

A New Single Chamber Implantable Defibrillator with Atrial Sensing: A Practical Demonstration of Sensing and Ease of Implantation

Abstract: Implantable cardioverter-defibrillators (ICDs) terminate ventricular tachycardia (VT) and ventricular fibrillation (VF) with high efficacy and can protect patients from sudden cardiac death (SCD). However, inappropriate shocks may occur if tachycardias are misdiagnosed. Inappropriate shocks are harmful and impair patient quality of life. The risk of inappropriate therapy increases with lower detection rates programmed in the ICD. Single-chamber detection poses greater risks for misdiagnosis when compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Since the patient had normal sinus rhythm and normal atrio-ventricular conduction, a single lead, Biotronik, Lumax 640 VR-T DX ICD was selected. A DX system consists of a single lead, which provides atrial as well as ventricular electrograms, and enhances atrial arrhythmia detection [1] . The patient was followed-up in the clinic and via the home monitoring service.…”
Section: Case Reportmentioning
confidence: 99%
“…Since the patient had normal sinus rhythm and normal atrio-ventricular conduction, a single lead, Biotronik, Lumax 640 VR-T DX ICD was selected. A DX system consists of a single lead, which provides atrial as well as ventricular electrograms, and enhances atrial arrhythmia detection [1] . The patient was followed-up in the clinic and via the home monitoring service.…”
Section: Case Reportmentioning
confidence: 99%
“…[18][19][20] However, data on sensing during rapidly conducted AF are scarce, and the only comparative study reported more atrial sensing problems with this method than a conventional atrial electrode (36% versus 11%; P=0.002).…”
Section: Single-lead Atrial Sensing Icdmentioning
confidence: 99%